Characterization of an endo-1, 3-fucanase from marine bacterium Wenyingzhuangia aestuarii: The first member of a novel glycoside hydrolase family GH174. (15th April 2023) - Liu, Guanchen; Shen, Jingjing; Chang, Yaoguang; Mei, Xuanwei; Chen, Guangning; Zhang, Yuying; Xue, Changhu
Abstract: Sulfated fucans are important marine polysaccharides with various biological and biomedical activities. Fucanases are favorable tools to establish the structure-activity relationships of sulfated fucans. Herein, gene fun174A was discovered from the genome of marine bacterium Wenyingzhuangia aestuarii OF219, and none of the pre-defined glycosidic hydrolase domains were predicted in the protein sequence of Fun174A. Recombinant Fun174A demonstrated a low optimal reaction pH at 5.5. It might degrade sulfated fucans in an endo -processive manner. Glycomics and NMR analyses proved that it specifically hydrolyzed α-1, 3-l -fucoside bonds between 2-O-sulfated and non-sulfated fucose residues in the sulfated fucan from sea cucumber Isostichopus badionotus . D119, E120 and E218 were critical for the activity of Fun174A, as identified by site-directed mutagenesis. Three homologs of Fun174A were confirmed to exhibit endo-1, 3-fucanase activities. The novelty on sequences of Fun174A and its homologs reveals a new glycoside hydrolase family, GH174. Graphical abstract: Unlabelled Image